Modernization and Social Change in Tajung Pademawu Village, Pamekasan - Alvind Meilinda Mulyadi; Taufik Hidayat; Syahrul Syah Al-Farizi; Siti Maryam (DAWUH : Islamic Communication Journal, 2025)
This study aims to describe the effect of modernization on social change as well as the inhibiting and supporting factors. The next goal is to uncover and explain the positive values ​​contained in modernization and social change. This research is a type of qualitative research that is descriptive. Informants were determined by purposive sampling. Data collection is done by; observation, interview, and documentation. As well as data analysis is carried out in stages; data reduction, data presentation and data verification. The results of the study explain that the influence of modernization on social change, namely; scientific thinking, and lifestyle changes. At first the people in meeting their daily needs, they took advantage of the natural surroundings. However, with the entry of modernization they began to follow the lifestyle that characterizes modern society. Several factors supporting the occurrence of modernization and social change, namely; heterogeneous society, dissatisfaction in various fields of life, and the perspective of humans who must improve their standard of living. While the inhibiting factors, namely; attitudes that are still traditional, the emergence of fear of wavering integration, and bad prejudice against elements of foreign culture. the influence of modernization on society in Tanjung Village, namely positive and negative influences. The positive influence of modernization can be seen in several fields, namely the fields of education, economy, socio-culture. Meanwhile, the people of Namlea village have always believed that everything can be calculated.Keywords: Modernization, Community Social Change,